(untitled) (Development Engineering Conferences Center Articles Database, 2025)
Building Information Modeling (BIM) is regarded as one of the most significant and innovative technologies to emerge in the fields of engineering, architecture, and construction. The application of this technology facilitates the development of a precise digital virtual representation of the structure. Building Information Modeling (BIM) is a methodology employed in the planning, design, construction, and operational phases of facilities. This technology enables architects, engineers, and construction professionals to effectively visualize the structures to be constructed within a simulated setting. This article examines contemporary approaches, advantages, possible hazards, and the obstacles that lie ahead.